Factors Related to Regional Recurrence in Early Stage Squamous Cell Carcinoma of the Oral Tongue - Soo-youn An; Eun-Jung Jung; Myungchul Lee; Tack-Kyun Kwon; Myung-Whun Sung; Yoon Kyung Jeon; Kwang Hyun Kim (Clinical and Experimental Otorhinolaryngology, 2008)
ObjectivesThis study analyzed various clinical and histopathologic factors for patients with early stage squamous cell carcinoma (SCC) of the oral tongue to define a high risk group for regional recurrence and finally to find out the indication of elective neck dissection (END).MethodsRetrospective chart review was performed for 63 patients with T1-T2N0 SCC of the oral tongue who underwent partial glossectomy with/without END. Clinical and histopathologic factors assessed were age, gender, clinical T stage, tumor cell differentiation, depth of invasion, pathologic nodal status, and intrinsic muscle involvement, perineural invasion, lymphovascular emboli and resection margin involvement.ResultsFive year overall survival rate was 97.1% in stage I and 76.2% in stage II, and 5-yr disease free survival rate was 76.7% in stage I and 43.5% in stage II. Rates of occult nodal metastasis in stage I and II were 15.4% and 42.9%, respectively. Overall regional recurrence rate was 15.9%, which consisted of 10.2% in stage I and 35.7% in stage II. The success rate of salvage treatment was 100% in stage I and 40% in stage II. Higher T stage, higher histologic grade, depth of invasion ≥3 mm, presence of intrinsic muscle involvement were significantly related to regional recurrence (P=0.035, P=0.011, P=0.016, P=0.009, respectively). In stage I, the non-END group (n=36) showed 13.9% of regional recurrence rate, while END group (n=13) did not have any regional recurrence (P=0.198). Five year disease free survival rate of END group was significantly higher than non-END group (100% and 68.7%, respectively, P=0.045).ConclusionWe recommend to perform END in early stage SCC of the oral tongue if the primary tumor has T2 stage, and T1 stage with higher histologic grade, depth of invasion more than 3 mm, or presence of intrinsic muscle involvement.